Efficacy and safety of eliapixant in diabetic neuropathic pain and prediction of placebo responders with an exploratory novel algorithm: results from the randomized controlled phase 2a PUCCINI study - Bouhassira, Didier; Tesfaye, Solomon; Sarkar, Arnab; Soisalon-Soininen, Sari; Stemper, Brigitte; Baron, Ralf (Pain, 2024)
Phase 2a of the PUCCINI study was a placebo-controlled, double-blind, parallel-group, multicenter, proof-of-concept study evaluating the efficacy and safety of the selective P2X3 antagonist eliapixant in patients with diabetic neuropathic pain (DNP) (ClinicalTrials.gov NCT04641273). Adults with type 1 or type 2 diabetes mellitus with painful distal symmetric sensorimotor neuropathy of >6 months' duration and neuropathic pain were enrolled and randomized 1:1 to 150 mg oral eliapixant twice daily or placebo for 8 weeks. The primary endpoint was change from baseline in weekly mean 24-hour average pain intensity score at week 8. In total, 135 participants completed treatment, 67 in the eliapixant group and 68 in the placebo group. At week 8, the change from baseline in posterior mean 24-hour average pain intensity score (90% credible interval) in the eliapixant group was -1.56 (-1.95, -1.18) compared with -2.17 (-2.54, -1.80) for the placebo group. The mean treatment difference was 0.60 (0.06, 1.14) in favor of placebo. The use of a model-based framework suggests that various factors may contribute to the placebo-responder profile. Adverse events were mostly mild or moderate in severity and occurred in 51% of the eliapixant group and 48% of the placebo group. As the primary endpoint was not met, the PUCCINI study was terminated after completion of phase 2a and did not proceed to phase 2b. In conclusion, selective P2X3 antagonism in patients with DNP did not translate to any relevant improvement in different pain intensity outcomes compared with placebo. Funding: Bayer AG.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Diabetic neuropathic pain; P2X3 antagonist; Painful diabetic peripheral neuropathy; Placebo response model; Type 1 diabetes mellitus; Type 2 diabetes mellitus